Relationship between the set outcome and the dig and attack efficacy in elite male Volleyball game - Monteiro, R.; Mesquita, I.; Marcelino, R. (International Journal of Performance Analysis in Sport, 2009)
The aim of this study was to analyze the relationship between the set outcome and the dig and attack efficacy in side-out transition in high competitive-level male volleyball. A total of 4351 sequences of game actions of the final phase of the Volleyball World Cup 2007 were analyzed. In order to test the association between those variables a chi-square test was carried out. The reliability showed percentages of agreement above the minimum indicated on the literature. The results showed a significant association between the attack efficacy and the set outcome since the teams that win the sets make fewer errors and have a higher efficacy in the counter-attack. The results also demonstrate that the dig efficacy is not significantly associated with the set outcome. The attack efficacy showed to be highly dependent of the dig efficacy since the frequency of attack points was higher when preceded by a perfect dig while the dig without all attack options is associated with the performance of attacks that allow continuity in the rally. Further research should analyze the efficacy of the remaining side-out transition phase game actions (the block and the set) and their relation with the set outcome.